Researchers’ View on R&D Organizational Change Using the Grief Cycle - Mia Rahma Romadona; Sigit Setiawan (STI Policy and Management Journal, 2021)
When change becomes a need, research and development organizations must likewise be adaptable to new challenges. The necessary changes will provide difficulties for management to manage human resource development. Failure, stagnation, or success is the eventual consequence of every organizational reform. Organizational changes are effective or unsuccessful based on the implementation strategies used, emphasizing the significance of human development managerial skills, leadership communication, and organizational interpersonal communication. This study aims to present an empirical study of changes occurring in research and development companies using grief cycle analysis. This research utilizes a variety of aspects and documents from prior studies to analyze the collective grief cycle phenomena associated with organizational changes in the R&D sector. The empirical description of the grieving cycle analysis demonstrates that the outcome of the grief cycle process indicates that the organization is not prepared to undertake changes, resulting in the crisis of certain workers. An empirical account of grieving cycle analysis reveals that time and the process of habituation play a significant influence in organizational members acceptance of changes in research and development organizations. Leadership communication and organizational interpersonal communication are critical in influencing organizational members' comprehension and acceptance of organizational goals and change processes.. Keywords: grief cycle, organizational change R&D, acceptance, HR management, leadership communication, organizational interpersonal communication